Effectiveness of Traffic Safety Education Among Students in Pontianak City: Case Study of Traffic Violations in 2023 - M Zainul Hafizi (International Journal of Applied Research and Sustainable Sciences, 2024)
This study aims to evaluate the effectiveness of traffic safety education among students in Pontianak City using a descriptive qualitative method. The results reveal a gap between knowledge and traffic rule application. Supervision, peer influence, and family roles significantly affect student behavior. Although students receive formal education, compliance relies on supervision and fear of sanctions. Interactive teaching methods proved more effective than theoretical approaches. A holistic approach involving schools, families, and law enforcement is necessary to enhance traffic awareness and compliance.